Gas diffusion layer and preparation method and application thereof
By using carbon-based loaded cerium oxide material in the microporous layer of the gas diffusion layer, the problems of poor durability of the gas diffusion layer and complex preparation process in the prior art are solved, and a more stable and uniform gas diffusion layer is achieved, which improves the service life and performance of the fuel cell.
Patent Information
- Application Number
- CN202411802434.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
The existing gas diffusion layer has poor durability and complex preparation process, making it difficult to maintain performance under high potential and acidic conditions.
A gas diffusion layer consisting of an overlapping base layer and a microporous layer, wherein the microporous layer is composed of a carbon-based cerium oxide material, a hydrophobic agent, a functional additive and a solvent. The cerium oxide is loaded on the carbon powder by chemical synthesis method, thereby improving the stability and uniformity of the layer.
It improves the durability and overall performance of the gas diffusion layer, extends the service life of the proton exchange membrane fuel cell, reduces the contact resistance, and enhances the durability under high potential and acidic conditions.
Smart Images

Figure CN119581580A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a gas diffusion layer and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) have the advantages of zero noise, zero emissions, long mileage, and rapid refueling, and are expected to become an important power source that can replace fossil fuels in the future transportation field. Among the factors that currently restrict its large-scale commercialization, in addition to cost and performance, durability is an issue that needs to be addressed urgently.
[0003] The fuel cell stack is composed of multiple layers of single cells connected in series, and each cell is composed of a proton exchange membrane (PEM), a catalyst layer (CL), a gas diffusion layer (GDL) and a bipolar plate. During the operation of the proton exchange membrane fuel cell (PEMFC), the H2O2 generated by the oxygen reduction reaction reacts with metal ions (such as Fe 2+ 、Co 2+ Under the catalysis of ions (such as ), it can be decomposed into hydroxyl radicals (·OH) and peroxide radicals (·OOH). The formed ·OH and ·OOH will attack the main chain and side chain of the proton membrane and release F - , making the proton membrane thinner, and even causing pinholes and cracks, leading to the failure of the proton exchange membrane fuel cell (PEMFC). CeO2 is considered to be the most effective free radical scavenger due to its excellent free radical scavenging performance. Since the generation sites of active free radicals are located in the catalyst layer and the membrane, most of them add CeO2 to the catalyst layer or proton exchange membrane (PEM). Although this method can effectively improve the durability of the membrane, it also greatly reduces the proton conductivity of the battery, thereby affecting the internal resistance and performance of the battery. Current research tends to add CeO2 to the microporous layer (MPL). On the one hand, the diffusion effect can be used to introduce cerium ions in the microporous layer (MPL) into the catalyst layer and the proton exchange membrane, thereby inhibiting the generation of active free radicals. On the other hand, this method can effectively prevent the proton conductivity of the battery from being affected because it greatly reduces the excessive occupation of proton conduction active sites by cerium ions. However, directly adding CeO2 into the microporous layer slurry does not make it evenly dispersed in the system, and cerium oxide easily falls off on the surface, resulting in poor uniformity and stability of the prepared gas diffusion layer.
[0004] In addition, the material that constitutes the microporous layer of the gas diffusion layer is mainly carbon material. Although carbon material is relatively corrosion-resistant, it is well known that when the potential is greater than 1V, carbon material is prone to electrochemical corrosion, and its corrosion rate increases exponentially with the increase of potential. If carbon corrosion occurs in the microporous layer, the pore structure will be destroyed, causing the loss of hydrophobic agent, thereby weakening the water vapor transmission capacity and affecting the electrical output performance. Therefore, carbon corrosion of the microporous layer is also an important research topic.
[0005] The prior art discloses depositing metallic cerium on the surface of a conventional microporous layer, so that a hydrophobic microporous layer containing nano-cerium oxide particles is deposited on the surface of the microporous layer, which can effectively capture the ·HO free radicals generated in the reaction when the fuel cell stack is running, prevent the degradation of the proton exchange membrane due to free radical attack, and improve the durability of the fuel cell membrane electrode. Although the deposited cerium oxide is located on the surface of the microporous layer and is in direct contact with the catalytic layer, the capture efficiency is greatly improved, but the electrophoretic deposition of the modified microporous layer on the conventional microporous layer not only increases the production time and production cost, but also has a complicated process and requires the introduction of a new production line - the electrodeposition production line, which is costly and not easy to industrialize. In addition, this technical solution cannot improve the durability of fuel cells under high potential and acidic conditions. Summary of the invention
[0006] The present application provides a gas diffusion layer and a preparation method and application thereof, aiming to solve the problems of poor durability and complicated preparation process of the existing gas diffusion layer.
[0007] In a first aspect, the present application provides a gas diffusion layer, comprising a substrate layer and a microporous layer that are overlapped;
[0008] The microporous layer comprises the following raw materials: a carbon-based cerium oxide-loaded material, a first hydrophobic agent, a functional additive and a solvent.
[0009] The microporous layer in the gas diffusion layer described in the present application contains cerium oxide. Cerium oxide is used as a free radical quencher. Cerium ions can partially migrate to the catalyst layer and proton exchange membrane of the fuel cell membrane electrode, quench the free radicals generated by it, and improve the durability of the membrane electrode; it can also effectively prevent the proton conductivity of the battery from being affected, which helps to improve the life of the proton membrane and the performance of the battery. The cerium oxide described in the present application is loaded on the carbon powder by a chemical synthesis method. This method of adding cerium oxide to the microporous layer is more stable and uniform than the gas diffusion layer formed by directly adding cerium oxide to the microporous layer slurry. The surface of the prepared gas diffusion layer is not easy to fall off cerium oxide, which is conducive to improving the durability of the gas diffusion layer and extending the service life of the proton exchange membrane fuel cell.
[0010] The addition of highly graphitized carbon powder loaded with cerium oxide into the microporous layer described in the present application not only improves the durability of the gas diffusion layer, but also reduces the contact resistance of the gas diffusion layer, thereby improving the overall performance of the gas diffusion layer.
[0011] According to some embodiments of the gas diffusion layer described in the present application, the substrate layer includes a hydrophobic carbon paper substrate layer or a hydrophobic carbon cloth substrate layer.
[0012] According to some embodiments of the gas diffusion layer described in the present application, the thickness of the substrate layer is 150-155 μm.
[0013] According to some embodiments of the gas diffusion layer described in the present application, the carbon-based cerium oxide-supported material includes carbon powder and cerium oxide supported on the carbon powder.
[0014] According to some embodiments of the gas diffusion layer described in the present application, the loading amount of cerium oxide in the carbon-based cerium oxide-loaded material is 5%-20%, preferably 15%-20%.
[0015] According to some embodiments of the gas diffusion layer described in the present application, the graphitization degree of the carbon powder is D / I G It is 0.3-2.0, preferably 0.3-0.5.
[0016] According to some embodiments of the gas diffusion layer described herein, the first hydrophobic agent includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and fluorinated ethylene propylene (FEP).
[0017] According to some embodiments of the gas diffusion layer described in the present application, the functional additive includes one or more of a pore former, a dispersant and a thickener.
[0018] According to some embodiments of the gas diffusion layer described in the present application, the pore-forming agent includes one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium oxalate and sodium bicarbonate; preferably, the dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and Triton; preferably, the thickener includes one or more of polyacrylamide, sodium carboxymethyl cellulose and sodium hydroxypropyl methyl cellulose.
[0019] According to some embodiments of the gas diffusion layer described in the present application, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, and isopropanol.
[0020] According to some embodiments of the gas diffusion layer described in the present application, the mass ratio of the carbon-based supported cerium oxide material and the first hydrophobic agent in the microporous layer is 1:(0.1-0.5).
[0021] According to some embodiments of the gas diffusion layer described in the present application, the mass ratio of the carbon-based supported cerium oxide material to the solvent is 1:(10-20).
[0022] According to some embodiments of the gas diffusion layer described in the present application, the mass ratio of the carbon-based supported cerium oxide material to the functional additive is 1:(0.01-0.05).
[0023] According to some embodiments of the gas diffusion layer described in the present application, the thickness of the microporous layer is 20-25 μm.
[0024] The second aspect of the present application provides a method for preparing the gas diffusion layer according to the first aspect of the present application, comprising the following steps:
[0025] (1) mixing a carbon-based supported cerium oxide material, a first hydrophobic agent, a functional additive and a solvent to obtain a microporous layer slurry;
[0026] (2) The microporous layer slurry is applied to a substrate layer, dried, and heat treated to obtain the gas diffusion layer.
[0027] The preparation method described in the present application is simple, low-cost, and easy to industrialize. The coating method used in the present application includes die coating, blade coating, or screen printing.
[0028] According to some embodiments of the preparation method described in the present application, in step (2), the drying temperature is 60-120° C., and the drying time is 10-20 min.
[0029] According to some embodiments of the preparation method described in the present application, the temperature of the heat treatment is 350-400° C., and the time of the heat treatment is 30-60 min.
[0030] According to some embodiments of the preparation method described in the present application, the substrate layer is a hydrophobic carbon paper substrate layer.
[0031] According to some embodiments of the preparation method described in the present application, the preparation method of the hydrophobic carbon paper substrate layer comprises the following steps:
[0032] a. contacting the carbon paper substrate with a hydrophobic liquid to perform a hydrophobic treatment on the carbon paper substrate;
[0033] b. Drying the hydrophobic treated carbon paper substrate and performing sintering treatment to obtain the hydrophobic carbon paper substrate layer.
[0034] According to some embodiments of the preparation method described in the present application, the hydrophobic liquid includes water and a second hydrophobic agent.
[0035] According to some embodiments of the preparation method described in the present application, the mass concentration of the second hydrophobic agent in the hydrophobic liquid is 3%-8%.
[0036] According to some embodiments of the preparation method described in the present application, the second hydrophobic agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride and ethylene propylene fluoride.
[0037] According to some embodiments of the preparation method described in the present application, in step b, the drying temperature is 60-120° C., and the drying time is 5-15 min; the sintering temperature is 250-350° C., and the sintering time is 5-15 min.
[0038] In a third aspect of the present application, a membrane electrode is provided, comprising the gas diffusion layer described in the first aspect of the present application or the gas diffusion layer obtained by the preparation method described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The vertical resistance of the gas diffusion layer under different pressures described in Example 1 and Example 3 of the present application;
[0040] Figure 2 This is a SEM image of the gas diffusion layer after electrochemical corrosion described in Example 1 of the present application;
[0041] Figure 3 This is a SEM image of the gas diffusion layer after electrochemical corrosion described in Example 3 of the present application;
[0042] Figure 4 This is a water contact angle diagram of the microporous layer of the gas diffusion layer described in Example 1 of the present application;
[0043] Figure 5 This is a water contact angle diagram of the microporous layer of the gas diffusion layer described in Example 3 of the present application. DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0045] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0046] The embodiment of the present application provides a gas diffusion layer, comprising a substrate layer and a microporous layer which are overlapped;
[0047] The microporous layer comprises the following raw materials: a carbon-based cerium oxide-loaded material, a first hydrophobic agent, a functional additive and a solvent.
[0048] The microporous layer in the gas diffusion layer described in the present application contains cerium oxide. Cerium oxide is used as a free radical quencher. Cerium ions can partially migrate to the catalyst layer and proton exchange membrane of the fuel cell membrane electrode, quench the free radicals generated by it, and improve the durability of the membrane electrode; it can also effectively prevent the proton conductivity of the battery from being affected, which helps to improve the life of the proton membrane and the performance of the battery. The cerium oxide described in the present application is loaded on the carbon powder by a chemical synthesis method. This method of adding cerium oxide to the microporous layer is more stable and uniform than the gas diffusion layer formed by directly adding cerium oxide to the microporous layer slurry. The surface of the prepared gas diffusion layer is not easy to fall off cerium oxide, which is conducive to improving the durability of the gas diffusion layer and extending the service life of the proton exchange membrane fuel cell.
[0049] The addition of highly graphitized carbon powder loaded with cerium oxide into the microporous layer described in the present application not only improves the durability of the gas diffusion layer, but also reduces the contact resistance of the gas diffusion layer, thereby improving the overall performance of the gas diffusion layer.
[0050] In some embodiments of the present application, the substrate layer includes a hydrophobic carbon paper substrate layer or a hydrophobic carbon cloth substrate layer.
[0051] In some embodiments of the present application, the thickness of the substrate layer is 150-155 μm, for example, 150 μm, 152 μm, 153 μm, 155 μm, etc.
[0052] In some embodiments of the present application, the carbon-based loaded cerium oxide material includes carbon powder and cerium oxide loaded on the carbon powder. The carbon-based loaded cerium oxide material of the present application is purchased from Shenzhen Bettery New Energy Materials Co., Ltd.
[0053] In some embodiments of the present application, the loading amount of cerium oxide in the carbon-based loaded cerium oxide material is 3%-20%, for example, 3%, 5%, 8%, 10%, 12%, 15%, 20%, etc.
[0054] In some embodiments of the present application, the loading amount of cerium oxide in the carbon-based cerium oxide material is 15%-20%. Because there is a catalytic layer between the gas diffusion layer and the proton exchange membrane, if the loading amount of cerium oxide in the microporous layer is less than 15%, it is difficult to effectively eliminate the free radicals generated during the operation of the battery in a timely manner. When the loading amount of cerium oxide in the microporous layer exceeds 20%, it is difficult to ensure the uniformity of the loading.
[0055] In some embodiments of the present application, the graphitization degree (I D / I G) is 0.3-2.0, such as 0.4, 0.6, 0.8, 1.0, 1.2, 1.6, 1.8, 2.0, etc. The graphitization degree of carbon powder refers to the degree to which carbon atoms form a close-packed hexagonal graphite crystal structure. The closer the lattice size is to the lattice constant of ideal graphite, the higher the graphitization degree. The I of carbon powder can be tested by Raman D / I G This data can measure the degree of graphitization of carbon powder. The lower the value, the higher the degree of graphitization.
[0056] Highly graphitized carbon powder is helpful to alleviate carbon corrosion, thereby improving the durability of fuel cells under high potential and acidic conditions. In addition, highly graphitized carbon powder has better conductivity, which can reduce contact resistance and improve interfacial electrochemical reactions. After high-temperature treatment, the thermal stability of highly graphitized carbon powder is enhanced, which helps to maintain the structural integrity and performance stability of the gas diffusion layer (GDL) during the operation of the proton exchange membrane fuel cell (PEMFC).
[0057] In some embodiments of the present application, the graphitization degree of the carbon powder is 0.3-0.5.
[0058] In some embodiments of the present application, the first hydrophobic agent includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and fluorinated ethylene propylene (FEP).
[0059] In some embodiments of the present application, the functional additives include pore formers, dispersants and thickeners.
[0060] In some embodiments of the present application, the pore-forming agent includes one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium oxalate and sodium bicarbonate; the dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and Triton; the thickener includes one or more of polyacrylamide, sodium carboxymethyl cellulose and sodium hydroxypropyl methyl cellulose.
[0061] In some embodiments of the present application, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, and isopropanol.
[0062] In some embodiments of the present application, the mass ratio of the carbon-based loaded cerium oxide material and the hydrophobic agent in the microporous layer is 1:(0.1-0.5); for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, etc.
[0063] In some embodiments of the present application, the mass ratio of the carbon-based supported cerium oxide material to the solvent is 1:(10-20); for example, 1:10, 1:12, 1:15, 1:16, 1:20, etc.
[0064] In some embodiments of the present application, the mass ratio of the carbon-based loaded cerium oxide material and the functional additive is 1:(0.01-0.05); for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, etc.
[0065] In some embodiments of the present application, the thickness of the microporous layer is 20-25 μm, for example, 20 μm, 21 μm, 23 μm, 25 μm, etc.
[0066] The present invention also provides a method for preparing a gas diffusion layer, comprising the following steps:
[0067] (1) mixing a carbon-based supported cerium oxide material, a hydrophobic agent, a functional additive and a solvent to obtain a microporous layer slurry;
[0068] (2) The microporous layer slurry is applied to a substrate layer, dried, and heat treated to obtain the gas diffusion layer.
[0069] The preparation method described in the present application is simple, low-cost, and easy to industrialize. The coating method used in the present application includes die coating, blade coating, or screen printing.
[0070] In some embodiments of the present application, in step (2), the drying temperature is 60-120°C, such as 60°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time is 10-20 minutes. The heat treatment temperature is 350-400°C, such as 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, etc., and the heat treatment time is 30-60 minutes.
[0071] In some embodiments of the present application, the substrate layer is a hydrophobic carbon paper substrate layer. The surface of carbon cloth is relatively rough and easily deformed under compression, which will bring a large contact resistance to the fuel cell. In addition, compared with carbon paper, carbon cloth itself is too soft and is prone to large deformation during the assembly of the membrane electrode and squeezed into the bipolar plate, causing the flow field of the bipolar plate to be blocked, which seriously reduces the performance of the fuel cell.
[0072] In some embodiments of the present application, the method for preparing the hydrophobic carbon paper substrate layer comprises the following steps:
[0073] a. contacting the carbon paper substrate with a hydrophobic liquid to perform a hydrophobic treatment on the carbon paper substrate;
[0074] b. Drying the hydrophobic treated carbon paper substrate and performing sintering treatment to obtain the hydrophobic carbon paper substrate layer.
[0075] The carbon paper substrate of the present application can be contacted with the hydrophobic liquid by immersion or vacuum adsorption. As a preferred embodiment, the carbon paper substrate is selected from Japanese Toray or Korean JNTG carbon paper.
[0076] In some embodiments of the present application, the hydrophobic liquid includes water and a second hydrophobic agent.
[0077] In some embodiments of the present application, the mass concentration of the second hydrophobic agent in the hydrophobic liquid is 3%-8%, for example, 3%, 5%, 6%, 8%, etc.
[0078] In some embodiments of the present application, the second hydrophobic agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride and fluorinated ethylene propylene.
[0079] In some embodiments of the present application, in step b, the drying temperature is 60-120°C, such as 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time is 5-15 min.
[0080] In some embodiments of the present application, the sintering temperature is 250-350°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 340°C, etc., and the sintering time is 5-15min.
[0081] An embodiment of the present application also provides a membrane electrode, comprising the gas diffusion layer described in the first aspect of the present application or the gas diffusion layer obtained by the preparation method described in the second aspect of the present application.
[0082] The gas diffusion layer was matched with a membrane electrode three-in-one assembly (manufactured by Guoqing Technology) and a conventional membrane electrode preparation process was used to prepare a membrane electrode (active area of 15×20 cm 2 ).
[0083] The microporous layer uses highly graphitized carbon powder loaded with cerium oxide material, which can improve the durability of PEM and GDL and extend the service life of PEMFC. At the same time, the addition of highly graphitized carbon powder can increase the conductivity of GDL and improve battery performance. The method is simple to prepare, low in cost and easy to industrialize.
[0084] The technical solution of this application is further explained below in conjunction with specific implementation cases and drawings.
[0085] Example 1
[0086] A gas diffusion layer and a method for preparing the same:
[0087] The gas diffusion layer comprises a substrate layer and a microporous layer which are overlapped, wherein the thickness of the substrate layer is 150 μm; and the thickness of the microporous layer is 20 μm.
[0088] The method for preparing the gas diffusion layer comprises the following steps:
[0089] (1) Preparation of substrate layer:
[0090] The ultrapure water and the second hydrophobic agent polytetrafluoroethylene are stirred and mixed evenly to obtain a hydrophobic liquid with a mass concentration of 5% of the second hydrophobic agent; the carbon paper substrate is immersed in the hydrophobic liquid to perform hydrophobic treatment to obtain a pre-treated substrate layer.
[0091] The pretreated substrate layer was dried at 80° C. for 10 min, and then sintered at 300° C. for 10 min to obtain a hydrophobic carbon paper substrate layer.
[0092] (2) Preparation of microporous layer slurry
[0093] The carbon-based cerium oxide material, the first hydrophobic agent polytetrafluoroethylene, the solvent water, the pore-forming agent ammonium carbonate, the dispersant polyvinyl pyrrolidone and the thickener polyacrylamide are mixed uniformly according to the mass ratio of 1:0.2:15:0.03:0.03:0.01 to obtain a microporous layer slurry; wherein the carbon-based cerium oxide material includes carbon powder and cerium oxide loaded on the carbon powder, and the loading amount of cerium oxide is 15%; the graphitization degree of the carbon powder is I D / I G is 0.3;
[0094] (3) Preparation of gas diffusion layer
[0095] The microporous layer slurry was coated onto the pretreated substrate layer by die coating, dried at 80° C. for 10 min, and then heat treated at 350° C. for 40 min to obtain a gas diffusion layer.
[0096] Example 2
[0097] The difference between the gas diffusion layer of Example 2 and the gas diffusion layer of Example 1 is that the graphitization degree of the carbon powder used in the preparation process of the gas diffusion layer of Example 2 is D / I G is 0.8.
[0098] Example 3
[0099] The difference between the gas diffusion layer of Example 3 and the gas diffusion layer of Example 1 is that the graphitization degree of the carbon powder used in the preparation process of the gas diffusion layer of Example 3 is D / I G is 1.3.
[0100] Example 4
[0101] The difference between the gas diffusion layer described in Example 4 and the gas diffusion layer described in Example 1 is that the loading amount of cerium oxide in the carbon-based cerium oxide-loaded material used in the preparation process of the gas diffusion layer described in Example 4 is 5%.
[0102] Example 5
[0103] The difference between the gas diffusion layer described in Example 5 and the gas diffusion layer described in Example 1 is that the loading amount of cerium oxide in the carbon-based cerium oxide-loaded material used in the preparation process of the gas diffusion layer described in Example 5 is 13%.
[0104] Example 6
[0105] The difference between the gas diffusion layer described in Example 6 and the gas diffusion layer described in Example 1 is that the loading amount of cerium oxide in the carbon-based cerium oxide-loaded material used in the preparation process of the gas diffusion layer described in Example 6 is 20%.
[0106] Comparative Example 1
[0107] The difference between the gas diffusion layer described in Comparative Example 1 and the gas diffusion layer described in Example 1 is that carbon powder is used instead of carbon-based cerium oxide material in the preparation process of the gas diffusion layer described in Comparative Example 1, and the graphitization degree of the carbon powder is D / I G is 0.3.
[0108] Comparative Example 2
[0109] The difference between the gas diffusion layer described in Comparative Example 2 and the gas diffusion layer described in Example 1 is that, in the preparation process of the gas diffusion layer described in Comparative Example 2, carbon powder and cerium oxide are used instead of the carbon-based supported cerium oxide material;
[0110] The specific operations are:
[0111] Carbon powder, cerium oxide, a first hydrophobic agent polytetrafluoroethylene, solvent water, a pore-forming agent ammonium carbonate, a dispersant polyvinyl pyrrolidone and a thickener polyacrylamide were mixed uniformly in a mass ratio of 1:0.15:0.2:15:0.03:0.03:0.01 to obtain a microporous layer slurry; the remaining operations were the same as in Example 1.
[0112] 1. Study on the electrochemical performance of Examples 1-6 and Comparative Examples 1-2 of the present application:
[0113] The single cell consists of a membrane electrode, a sealing gasket, a flow field plate, a collector plate, and an end plate. The membrane electrode consists of a proton membrane, a catalyst layer, and a diffusion layer. The active area of the membrane electrode used in this paper is 15×20 cm 2 The proton membrane is produced by Wuhan Green Power, and the cathode and anode catalysts are produced by Guohydrogen Technology.
[0114] OCV operating conditions and characterization methods
[0115] The OCV (Open Circuit Voltage) condition refers to the situation where hydrogen and air are introduced into the anode and cathode of the PEMFC respectively, but the discharge is not performed through an external circuit. The OCV test conditions refer to the accelerated test program of the U.S. Department of Energy (DOE), and the specific test conditions are shown in Table 2. In this experiment, the PEMFC activation and OCV tests were performed on the fuel cell test system of Dalian Ruige Company.
[0116] After the OCV condition was completed, the cross-sectional structure of the membrane electrode was observed using SEM to obtain the proton membrane thickness data.
[0117] The test results are shown in Table 1:
[0118] Table 1
[0119]
[0120]
[0121] Table 2 OCV working condition test conditions
[0122]
[0123] It can be seen from Table 1 that when the cerium oxide loading is 15-20%, the thickness of the proton membrane remains basically unchanged, and the hydrogen permeation current density increases the least, indicating that at this loading, cerium ions can effectively eliminate free radicals generated during battery operation, protect the proton membrane, and increase the durability of the proton membrane.
[0124] 2. The vertical resistance test of the gas diffusion layer includes the following equipment and tools
[0125] Equipment-TRI Planar Material Analyzer
[0126] Tools-Standard Cutting Die
[0127] Sample preparation
[0128] Use the standard mold to randomly cut 3 pieces of 15.4cm in size from the sample. 2 The sample to be tested is a circular ring (diameter: φ4.5cm–φ0.8cm). The number of samples is 3, and the samples are required to be free of scratches and damage.
[0129] The sample to be tested is placed centrally on the two gold-plated copper disk circular tables of the TRI planar material analyzer with the MPL facing upwards, and the vertical resistance under different pressures is tested.
[0130] Test results such as Figure 1 shown.
[0131] from Figure 1 It can be seen that the contact resistance of the gas diffusion layer described in Example 1 of the present application is significantly reduced compared with the gas diffusion layer described in Example 3, that is, the addition of highly graphitized materials can improve the contact performance of the gas diffusion layer and reduce the contact resistance.
[0132] 3. Study on the corrosion resistance of the gas diffusion layer described in this application:
[0133] Research method: In 0.5M H2SO4, the gas diffusion layers described in Example 1 and Example 3 of the present application were used as working electrodes (1.4V vs. SCE), saturated calomel electrode and graphite rod were used as reference electrode and counter electrode respectively. After electrochemical corrosion for 500h, the SEM images of the gas diffusion layers described in Example 1 and Example 3 were as follows: Figure 2 and Figure 3 shown.
[0134] from Figure 2 and Figure 3 It can be seen that: after the electrochemical corrosion test, the surface structure of the microporous layer of the gas diffusion layer described in Example 1 of the present application remains intact without showing any obvious signs of corrosion, while the surface of the microporous layer of the gas diffusion layer described in Example 3 has shown obvious carbon corrosion, with grooves and voids appearing on the surface; that is, the gas diffusion layer described in the present application has better corrosion resistance.
[0135] 4. Use a contact angle tester to test the static water contact angle of GDL to characterize its hydrophobicity. The specific operation process is as follows:
[0136] 1) Sample preparation: Cut the GDL sample into small pieces that fit the size of the sample stage;
[0137] 2) Equipment calibration and setting: Use a standard ball to calibrate the contact angle tester. After the calibration is completed, open the test interface and set the test liquid to deionized water and the test droplet size to 10 μL;
[0138] 3) Sample placement: Place the sample in the center of the test bench and use the sample clamps on the bench to fix both sides of the sample to make it level, ensuring that the sample is placed flat without wrinkles or distortions;
[0139] 4) Sample testing:
[0140] ① Hang a 10μL water droplet at the end of the pipette tip and drop it steadily on the sample surface;
[0141] ②Measure the contact angle after the water droplet is stable on the sample surface for ≥5s. The high-speed camera takes a picture of the water droplet and measures the contact angle.
[0142] ③ Move the test sample, drop the next drop of water on the new test part of the sample, and repeat the above steps to test the contact angle;
[0143] ④ Open the analysis software and read the contact angle value after the droplet has been stable for 5 seconds.
[0144] The average contact angle of the MPL at 6 test points was taken as the final contact angle of the microporous layer of the GDL sample.
[0145] The water contact angle diagrams of the microporous layer of the gas diffusion layer in Example 1 and Example 3 are shown as follows: Figure 4 and Figure 5 shown.
[0146] from Figure 4 and Figure 5 It can be seen that the gas diffusion layer described in Example 1 of the present application still remains hydrophobic, maintaining the original structure and function of the gas diffusion layer; while the surface of the gas diffusion layer described in Example 3 has become hydrophilic after corrosion, and the structural integrity of the GDL is lost.
[0147] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A gas diffusion layer, characterized in that: It includes a substrate layer and a microporous layer which are overlapped; The microporous layer comprises the following raw materials: a carbon-based cerium oxide-loaded material, a first hydrophobic agent, a functional additive and a solvent.
2. The gas diffusion layer according to claim 1, characterized in that The substrate layer comprises a hydrophobic carbon paper substrate layer or a hydrophobic carbon cloth substrate layer; And / or, the substrate layer has a thickness of 150-155 μm.
3. The gas diffusion layer according to claim 1, characterized in that: The carbon-based cerium oxide-loaded material comprises carbon powder and cerium oxide loaded on the carbon powder; Preferably, the loading amount of cerium oxide in the carbon-based cerium oxide-loaded material is 5%-20%, preferably 15%-20%; Preferably, the graphitization degree of the carbon powder (I D / I G ) is 0.3-2.0, preferably 0.3-0.
5.
4. The gas diffusion layer according to claim 1, characterized in that: The first hydrophobic agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride and fluorinated ethylene propylene; And / or, the functional additives include one or more of a pore former, a dispersant and a thickener; preferably, the pore former includes one or more of ammonium carbonate, ammonium bicarbonate, ammonium chloride, ammonium oxalate and sodium bicarbonate; preferably, the dispersant includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and Triton; preferably, the thickener includes one or more of polyacrylamide, sodium carboxymethyl cellulose and sodium hydroxypropyl methyl cellulose; And / or, the solvent includes one or more of water, ethanol, ethylene glycol, n-propanol, and isopropanol.
5. The gas diffusion layer according to any one of claims 1 to 4, characterized in that: The mass ratio of the carbon-based supported cerium oxide material and the first hydrophobic agent in the microporous layer is 1:(0.1-0.5); And / or, the mass ratio of the carbon-based supported cerium oxide material to the solvent is 1:(10-20); And / or, the mass ratio of the carbon-based supported cerium oxide material to the functional additive is 1:(0.01-0.05); And / or, the microporous layer has a thickness of 20-25 μm.
6. The method for preparing a gas diffusion layer according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing a carbon-based supported cerium oxide material, a first hydrophobic agent, a functional additive and a solvent to obtain a microporous layer slurry; (2) The microporous layer slurry is applied to a substrate layer, dried, and heat treated to obtain the gas diffusion layer.
7. The method for preparing a gas diffusion layer according to claim 6, characterized in that: In step (2), the drying temperature is 60-120° C. and the drying time is 10-20 min; And / or, the temperature of the heat treatment is 350-400° C., and the time of the heat treatment is 30-60 min.
8. The method for preparing a gas diffusion layer according to claim 6, characterized in that: The substrate layer is a hydrophobic carbon paper substrate layer; Preferably, the method for preparing the hydrophobic carbon paper substrate layer comprises the following steps: a. contacting the carbon paper substrate with a hydrophobic liquid to perform a hydrophobic treatment on the carbon paper substrate; b. Drying the hydrophobic treated carbon paper substrate and performing sintering treatment to obtain the hydrophobic carbon paper substrate layer.
9. The method for preparing a gas diffusion layer according to claim 8, characterized in that: The hydrophobic liquid includes water and a second hydrophobic agent; Preferably, the mass concentration of the second hydrophobic agent in the hydrophobic liquid is 3%-8%; Preferably, the second hydrophobic agent includes one or more of polytetrafluoroethylene, polyvinylidene fluoride and fluorinated ethylene propylene. And / or, in step b, the drying temperature is 60-120° C., and the drying time is 5-15 min; The sintering temperature is 250-350° C., and the sintering time is 5-15 minutes.
10. A membrane electrode, characterized in that: The invention comprises the gas diffusion layer according to any one of claims 1 to 5 or the gas diffusion layer obtained by the preparation method according to any one of claims 6 to 9.